2016
DOI: 10.1001/jamacardio.2016.1161
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Outcomes of Anemia and Hematinic Deficiencies in Patients With Chronic Heart Failure

Abstract: Anemia is common in patients with HF and often associated with iron deficiency. Both anemia and iron deficiency are associated with an increase in all-cause and cardiovascular mortality and might both be therapeutic targets in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
131
2
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(143 citation statements)
references
References 35 publications
6
131
2
4
Order By: Relevance
“…When analyzed according to hemoglobin level, 46% of those without anemia and 61% of those with anemia were iron‐deficient . These results are similar to a recently published study of 4456 patients referred to a single outpatient heart failure service, which identified iron deficiency in 43%‐68% of patients with anemia and 14%‐35% of those with a normal hemoglobin depending on the definition of iron deficiency used . There has only been one published study using the gold standard technique of bone marrow analysis, which examined 37 anemic patients with advanced severe heart failure and demonstrated iron deficiency in 73% …”
Section: Prevalence and Prognosis Of Iron Deficiency In Heart Failuresupporting
confidence: 80%
See 1 more Smart Citation
“…When analyzed according to hemoglobin level, 46% of those without anemia and 61% of those with anemia were iron‐deficient . These results are similar to a recently published study of 4456 patients referred to a single outpatient heart failure service, which identified iron deficiency in 43%‐68% of patients with anemia and 14%‐35% of those with a normal hemoglobin depending on the definition of iron deficiency used . There has only been one published study using the gold standard technique of bone marrow analysis, which examined 37 anemic patients with advanced severe heart failure and demonstrated iron deficiency in 73% …”
Section: Prevalence and Prognosis Of Iron Deficiency In Heart Failuresupporting
confidence: 80%
“…Major gaps of knowledge still exist. Although serum ferritin has been used in several of the studies, increasing amounts of data suggest that serum ferritin is not a robust indicator of iron deficiency . Patients with CHF are less likely to have a low serum ferritin compared to patients without CHF.…”
Section: Future Challengesmentioning
confidence: 99%
“…The prevalence of anaemia in HF has previously been reported in European studies to range between 16% and 53% . Differences in characteristics of the study populations could account for this wide range in prevalence.…”
Section: Discussionmentioning
confidence: 86%
“…The causes of anaemia in HF are multifactorial, and its impact on quality of life (QoL) and outcomes may vary by ethnic background. Prior reports are mainly from Western populations, where the prevalence of anaemia in patients with heart failure with reduced ejection fraction has been reported to range between 16% and 34%, and anaemia has been shown to contribute independently to morbidity and mortality . Prevalence of anaemia is higher in the general population of Asian compared with Western countries and varies widely across Asia .…”
Section: Introductionmentioning
confidence: 99%
“…Higher Fe stores have also been positively associated with risk factors for CD, such as type 2 diabetes mellitus . In addition, Fe deficiency is one of the major risk factors for disability and mortality worldwide, and it was identified as a common and ominous comorbidity in patients with heart failure . The heart is a major organ where Fe accumulates in situation of overload.…”
Section: Introductionmentioning
confidence: 99%